Utilization of Sentinel-1 Imagery for Mapping the Distribution of Floods in the Putussibau Kota Subdistrict and Surrounding Areas - Tantri, Oktaviana; Sampurno, Joko; Adriat, Riza (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
Floods are a disaster that often occurs in the Putussibau Kota sub-district, West Kalimantan, because of its location where the Kapuas River passes. However, flood disaster mitigation efforts in this area are often hampered by the lack of information on flood distribution maps and impact predictions. This research utilizes the change detection and thresholding (CDAT) method applied to Sentinel-1 SAR data to map the distribution of floods in the Putussibau Kota sub-district and its surroundings, as well as analyze its impact on infrastructure and population. Next, the impact of the flood is calculated using an overlay technique between the flood map and the exposure map. The research results show that the flood distribution map for the August 2021 event had an accuracy of 0.76 and a kappa coefficient of 0.52. Next, the results of the flood impact evaluation showed that 37 km of roads, 2,700 buildings, and 11,700 people were affected by this incident. This analysis can be used to assist local governments in future flood mitigation efforts.